Pengaruh Model Pembelajaran Course Review Horay (CRH) Terhadap Hasil Belajar Matematika Siswa Kelas V SD - Tiyas, Melati Ayuning; Wardiah, Dessy; Kuswidyanarko, Arief (ANTHOR: Education and Learning Journal, 2022)
The problem in this study is the lack of student activity during the learning process, the lack of student interest in learning Mathematics and the lack of use of learning models, causing low student learning outcomes. This study aims to determine the effect of the Course Review Horay (CRH) learning model on the Mathematics Learning Outcomes of Fifth Grade Elementary School Students. The population in this study were all fifth grade students of SDNegeri 23 Palembang. This research is a quantitative research with experimental method with the form of research design that is Posttest-Only Control Design. Sampling using random sampling method, Data collection techniques in this study are tests, observations anddocumentation. The data analysis technique in this research is using the Paired Sample t-test. The results of the calculation of data analysis obtained that the control class posttest average value was 46.6 with the Unfinished category and the experimental class posttest average valuewas 85.7 with the Completed category and hypothesis testing using the Paired Sample t-Test which showed that the sig value 2-tailed= 0.000 < 0.05. This proves that the Course Review Horay (CRH) learning model has an effect on the mathematics learning outcomes of fifth grade elementary school students. Then the Course Review Horay (CRH) learning model can be a solution in improving student learning outcomes in the Mathematics subject matter of spatial construction.